A novel species of lactic acid bacteria, Ligilactobacillus pabuli sp. nov., isolated from alfalfa silage. Issue 10 (21st October 2022) - Tohno, Masanori; Tanizawa, Yasuhiro; Sawada, Hiroyuki; Sakamoto, Mitsuo; Ohkuma, Moriya; Kobayashi, Hisami
Abstract : In this study, we isolated a novel strain of lactic acid bacteria, AF129 T, from alfalfa silage prepared locally in Morioka, Iwate, Japan. Polyphasic taxonomy was used to characterize the bacterial strain. The bacterium was rod-shaped, Gram-stain-positive, non-spore-forming and catalase-negative. The strain grew at various temperatures (15–40°C) and pH levels (4.0–8.0). The optimum growth conditions were a temperature of 30°C and a pH of 6.0. AF129 T exhibited growth at salt (NaCl) concentrations of up to 6.5 % (w/v). The G+C content of the strain's genomic DNA was 41.5 %. The major fatty acids were C16 : 0, C18 : 1 ω9 c, C19 : 0 cyclo ω8 c and summed feature 8. 16S rRNA gene sequencing revealed that AF129 T represents a member of the genus Ligilactobacillus and it has higher sequence similarities with Ligilactobacillus pobuzihii (98.4 %), Ligilactobacillus acidipiscis (97.5 %) and Ligilactobacillus salitolerans (97.4 %). The digital DNA–DNA hybridization values for AF129 T and phylogenetically related species of the genus Ligilactobacillus ranged from 19.8% to 24.1%. The average nucleotide identity of the strain with its closely related taxa was lower than the threshold (95 %–96 %) used for species differentiation. In the light of the above-mentioned physiological, genotypic, chemotaxonomic and phylogenetic evidence, we confirm that AF129 T represents a member of the genus Ligilactobacillus and constitutes a novel species; we propose the name Ligilactobacillus pabuli sp. nov. for this species. The type strain is AF129 T =MAFF 518002 T =JCM 34518 T =BCRC 81335 T .